Grating Spectrum Design and Optimization of GMM-FBG Current Sensor - Fei Jiao; Yuqing Lei; Guozheng Peng; Funing Dong; Qing Yang; Wei Liao (Energies, 2023)
In this study, the performance of a current sensor based on giant magnetostrictive materials (GMM) and fiber Bragg grating (FBG) has been improved by optimizing the spectral characteristics of gratings. By analyzing the influence of FBG on the current sensor characteristics, three key parameters (gate region length, refractive index modulation depth, and toe cutting system) are selected for optimization. The optimal grating parameters are determined to improve the linearity and sensitivity of sensor output. Experimental tests reveal that after grating optimization, the current sensor shows excellent performance parameters, including a linearity of 0.9942, sensitivity of 249.75 mV/A, and good stability in the temperature range of 0–60 °C. This research can provide a reference for improving the grating design and performance of existing GMM-FBG current sensors.